2010
DOI: 10.1111/j.1467-7687.2009.00884.x
|View full text |Cite
|
Sign up to set email alerts
|

Biological components of colour preference in infancy

Abstract: Adult colour preference has been summarized quantitatively in terms of weights on the two fundamental neural processes that underlie early colour encoding: the S-(L+M) ('blue-yellow') and L-M ('red-green') cone-opponent contrast channels (Ling, Hurlbert & Robinson, 2006; Hurlbert & Ling, 2007). Here, we investigate whether colour preference in 4-5-month-olds may be analysed in the same way. We recorded infants' eye-movements in response to pairwise presentations of eight colour stimuli varying only in hue. Inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
59
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(76 citation statements)
references
References 33 publications
14
59
0
Order By: Relevance
“…For both light and dark colors, the highest and lowest preferences were significantly different from chance. This finding might explain the differences among previous infant studies (Adams, 1987;Bornstein, 1975;Franklin et al, 2010;Franklin et al, 2008;Teller et al, 2004;Zemach et al, 2007), because the lightnesses (and saturations) of colors were different in each study.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…For both light and dark colors, the highest and lowest preferences were significantly different from chance. This finding might explain the differences among previous infant studies (Adams, 1987;Bornstein, 1975;Franklin et al, 2010;Franklin et al, 2008;Teller et al, 2004;Zemach et al, 2007), because the lightnesses (and saturations) of colors were different in each study.…”
Section: Resultsmentioning
confidence: 69%
“…However, EVT also proposes that an innate, adaptive function of color preferences could draw us toward objects that are evolutionarily beneficial (e.g., clean water), and away from those that are not (e.g., rotten food). Previous research on infant color preferences has been consistent with the innateness hypothesis, in that young infants preferentially look most at blue and least at yellow-green or yellow (e.g., Adams, 1987;Bornstein, 1975;Franklin, Bevis, Ling, & Hurlbert, 2010;Franklin et al, 2008;Teller, Civan, & Bronson-Castain, 2004;Zemach, Chang, & Teller, 2007). The similarity between infant hue preference curves in these studies and those in their adult study led Palmer and Schloss (2010) to suggest that at least some aspects of adult color preference may be innate.…”
Section: ) Several Theories Have Recently Been Proposed About Whmentioning
confidence: 63%
See 2 more Smart Citations
“…Hurlbert and Ling suggested that women weight more positively on the L-M axis, due to their early roles as gatherers in hunter-gatherer societies (e.g., needing to find red berries against green leaves). This sex difference in weightings on the L-M axis was not corroborated in other cultures, however (Taylor, Clifford, & Franklin, 2013;Yokosawa, Schloss, Asano, & Palmer, 2015) or in infants (Franklin, Bevis, Ling, & Hurlbert, 2009), which challenges the gender-based evolutionary account for different weightings across individuals. How and why individual differences in color preferences arise, therefore, remain open questions.…”
Section: Biological Accounts Of Individual Differencesmentioning
confidence: 76%